Biosurfaces : a materials science and engineering perspective - Balani, Kantesh (Hoboken, New Jersey : ACerS--Wiley, 2014)
'Ideal as a graduate textbook, this book is aimed at helping design effective biomaterials, taking into account the complex interactions that occur at the interface when a synthetic material is inserted into a living system. Surface reactivity, biochemistry, substrates, cleaning, preparation, and coatings are presented, with numerous case studies and applications throughout. Highlights include: Starts with concepts and works up to real-life applciations such as implantable devices, medical devices, prosthetics, and drug delivery technology Addresses surface reactivity, requirements for surface coating, cleaning and preparation techniques, and characterization Discusses the biological response to coatings Addresses biomaterial-tissue interaction Incorporates nanomechanical properties and processing strategies'--
'This book is aimed at helping design effective biomaterials, taking into account the complex interactions that occur at the interface when a synthetic material is inserted into a living system. Surface reactivity, biochemistry, substrates, cleaning, preparation, and coatings are presented, with numerous case studies and applications throughout'--
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Surfaces (Technology); Biomedical materials; Electronic books